2005
DOI: 10.1063/1.1925781
|View full text |Cite
|
Sign up to set email alerts
|

Selective epitaxial growth of submicron complex oxide structures by amorphous SrTiO3

Abstract: A chemical-free technique for fabricating submicron complex oxide structures has been developed based on selective epitaxial growth. The crystallinity and hence the conductivity of the complex oxide is inhibited by amorphous SrTiO3 (STO). Using a combination of pulsed laser deposition and electron-beam lithography, amorphous STO barriers are first deposited on a single crystal substrate. A thin film is then deposited on the patterned substrate with the amorphous STO barriers acting to electrically and physical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The further study by Abdelhadi et al [9] revealed that this physical phenomenon was induced by the Phase Slip. The I V curves of the microbridge structures fabricated by Morales et al [10] show S figures, which is consistent with the superconductive phase slippage theory. By investigating into La 0.67 Ca 0.33 MnO 3 (LCMO) micro-bridges made with the same method, it was found that the metal-to-insulator temperature was depressed with the decrease of the width of the bridge.…”
supporting
confidence: 81%
“…The further study by Abdelhadi et al [9] revealed that this physical phenomenon was induced by the Phase Slip. The I V curves of the microbridge structures fabricated by Morales et al [10] show S figures, which is consistent with the superconductive phase slippage theory. By investigating into La 0.67 Ca 0.33 MnO 3 (LCMO) micro-bridges made with the same method, it was found that the metal-to-insulator temperature was depressed with the decrease of the width of the bridge.…”
supporting
confidence: 81%
“…In general, any of the above scenarios may lead to local regions containing a weakened OP, with respect to phase fluctuations. In this connection, it is worth noting that such weakened regions could also be nucleation centers for phase-slip phenomena, which were seen in recent transport studies on superconducting YBCO microstrips 33,34 . It should also be remarked that our discussion of lowenergy Andreev states is not limited to only specular cases.…”
Section: Discussionmentioning
confidence: 99%
“…SrTiO 3 films have also been used as template for the growth of submicron structures. Both amorphous [53] and porous [54] SrTiO 3 have been used to integrate nanostructures of YBCO in macroscale structures. These techniques have the advantage of reducing the structural damage, but present limited control over the position, dimensions and shape of the nanostructures.…”
Section: Ybco Nanowire Fabrication and Characterizationmentioning
confidence: 99%